2009
DOI: 10.1590/s1807-59322009000800010
|View full text |Cite
|
Sign up to set email alerts
|

Comorbidities in Severe Asthma: Frequency of Rhinitis, Nasal Polyposis, Gastroesophageal Reflux Disease, Vocal Cord Dysfunction and Bronchiectasis

Abstract: OBJECTIVESSevere asthma is found in approximately 10% of patients with asthma. Some factors associated with worse asthma control include rhinitis, gastroesophageal reflux disease, vocal cord dysfunction (VCD), nasal polyposis and bronchiectasis. Therefore, we evaluated the prevalence of these illnesses in patients with severe asthma.METHODSWe conducted a retrospective analysis of data obtained from electronic medical records of patients with severe asthma between January 2006 and June 2008. Symptoms of rhiniti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
59
0
3

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(65 citation statements)
references
References 28 publications
3
59
0
3
Order By: Relevance
“…Discussion There was negative correlation between AQLQ and RSI , and between ACT and RSI. These results are in accordance with the recent studies [3,5]. Cheung and his colleagues showed that, a significant proportion of asthmatic patients in Hong Kong have gastroesophageal reflux disease (GERD), and this is associated with poorer asthmatic control, quality of life, and psychological status [3].…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…Discussion There was negative correlation between AQLQ and RSI , and between ACT and RSI. These results are in accordance with the recent studies [3,5]. Cheung and his colleagues showed that, a significant proportion of asthmatic patients in Hong Kong have gastroesophageal reflux disease (GERD), and this is associated with poorer asthmatic control, quality of life, and psychological status [3].…”
Section: Resultssupporting
confidence: 89%
“…Therefore, finding and elimination of these influencing factors are one of the priorities. There is a considerable evidence that, special medical conditions affect asthma managing, such as gastroesophageal reflux, allergic rhinitis, infections, surgery, obesity related comorbidities like obstructive sleep apnea [2][3][4][5][6]. Association of asthma with gastroesophageal reflux and allergic rhinitis is well known.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The prevalence of bronchiectasis in patients with severe asthma is relatively high; with 25–40% of patients having radiological signs of bronchiectasis [91,92], compared to 3% in a population of generally milder asthma [93]. …”
Section: Systematic Assessment Of Severe Asthmamentioning
confidence: 99%
“…(3) In a review article, Giavina-Bianchi et al described the principal characteristics of difficult-to-control asthma and a protocol for its management. (4) Dalcin et al studied the prevalence of controlled asthma, partially controlled asthma, and uncontrolled asthma (56%, 27%, and 17%, respectively) and found that greater asthma severity, limited availability of medications, and no inhaled corticosteroid use were factors associated with poor disease control.…”
Section: Introductionmentioning
confidence: 99%